Estratégias para aumentar a conectividade e o desempenho das VANETs: infraestrutura baseada no transporte coletivo e protocolos - Alves Junior, Joilson (2016)
Vehicular Ad Hoc Networks (VANETs) are mobile networks which have as a purpose the communication between vehicles in order to provide safety and entertainment to their users. The communication may occur in three ways: Vehicle-to-Vehicle (V2V), Vehicle-to-Infrastructure (V2I) and hybrid (V2V and V2I at the same time). V2I and hybrid networks have, usually, high costs of implementation and maintenance, for they need to be implemented in places with a fixed infrastructure, which will be impracticable most of the times. V2V networks, on the other hand, have low cost of implementation, for they may be implemented in any urban nvironment. However, V2V networks would depend on the vehicles flow in order to keep connectivity and a good performance. In urban environments there are basically private vehicles, cargo vehicles and public transport vehicles (buses). Of these, the public transport vehicles present a distinct behavior in regard to other vehicles. Specifically, in the city of Curitiba, the buses from express lines travel in exclusive lanes, following a relatively regular schedule, in a linear route with practically no obstacles. These characteristics suggest that a system using those buses for the deployment of a communication infrastructure would present a superior performance if compared to a system which makes no distinction between vehicles. Thus, this work proposes the utilization of public transport urban buses for the implementation of an mobile backbone (BMVA), which will provide connectivity and improve the network performance without using a fixed infrastructure. New routing protocols, capable of exploring the intrinsic connectivity provided by BMVA are also proposed. These protocols were developed from AODV, AOMDV and DSDV protocols. Statistical analyses with real data and simulation experiments, confirm that BMVA and the new protocols can create a mobile communication infrastructure and increase the performance metrics such as delivery rate and throughput.